Knowledgeable, aware / interested: Young black women's perceptions of pre-exposure prophylaxis - Haider, Sadia; Friedman, Eleanor E.; Ott, Emily; Moore, Amy; Pandiani, Agustina; Desmarais, Catherine; Johnson, Amy K. (Frontiers in Reproductive Health, 2022)
Purpose HIV in the United States disproportionately affects young Black women. Pre-exposure prophylaxis (PrEP) is an effective HIV prevention option that has the potential to reduce HIV incidence among HIV-vulnerable populations. However, data regarding women's awareness, interest in starting, and feelings of acceptability or stigma about PrEP remains limited, particularly among adolescent and young Black women. Materials and methods A cross-sectional survey was conducted with 100 sexually active young Black women ages 13–24 years attending women's health clinics in Chicago, IL. Descriptive statistics were used to characterize the sample and determine more about what the PrEP needs and barriers are in this community. Associations were modeled using logistic regression and 95% confidence intervals for both bivariate and multivariable models. Results In our survey (N = 100), half of study participants (50%) expressed interest in starting PrEP in the next three months and a majority (80%) of young women were confident they could obtain PrEP. Pregnant young women were significantly more interested in starting PrEP than non-pregnant women [OR 2.3 95% CI (1.0, 5.4)], p = 0.05), however, this association did not remain significant in adjusted models. Conclusions This study provides a more complete understanding of awareness, interest in, and acceptability of PrEP among adolescent and young Black women attending women's health clinics. Findings indicate sustained interest in starting PrEP, reduced stigma, and increased awareness of PrEP among young Black women. These findings suggest that integrating PrEP into women's health clinics is a promising strategy to increase awareness and utilization of PrEP and decrease HIV transmission among youth at highest risk.